STUDIES ON ENVIRONMENTAL ETHICS FOR STUDENTS IN INDONESIA - Aldiansyah, Rifki; Ariyansyah, Irvan; Efriani, Efriani; Dewantara, Jagad Aditya; Sulistyarini, Sulistyarini; Sudagung, Aditya Darmawan (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
Environmental ethics  is human-wise behavior related to all components of the environment. Environmental ethics talks about human behavior towards nature and the view of the universe, including nature, humans, and other living things. A moral view is needed to know the relevance of the theory of anthropocentrism and ecocentrism. Students must know which theories can benefit human life and how to maintain a balance between nature and humans. Belief in the theory will bring up pros and cons; therefore, the relevance that can be found from the two theories is education that understands environmental ethics as a balance. Relevance gained trust in these two theories will bring up pros and cons. We found out students in Indonesia had their main critizism towards each philosophical thought. We also found that the emerging technology and modernisation has been an issue on the debate. A better environmental ethics understanding would serve a better goal of balancing both view of   anthropocentrism and ecocentrism